P-090 YI Assessing Provider Documentation of Inflammatory Bowel Disease Quality Measures. (March 2016) - Rawl, Rebecca; Cheng, Jianfeng; Scobey, Martin; Ikanovic, Jasna; Goodwin, Aaron
Abstract : Background: Inflammatory bowel disease is characterized by chronic inflammation with episodic flares. The goal of IBD treatment is to achieve remission and control of symptoms while minimizing morbidity from the underlying disease and treatment side effects. Approximately 1.4 million Americans are affected by IBD and these visits account for 700, 000 outpatient and 100, 000 inpatient visits per year with an estimated healthcare cost of 1.7 billion/year. Given the high costs and morbidity associated with IBD, the AGA established the 2011 "Adult Inflammatory Bowel Disease Physician Performance Measures Set" as a framework for high-quality IBD care. The 8 outpatient core measures include: (1) IBD type, anatomic location and activity all documented; (2) Corticosteroid-sparing therapy; (3) Corticosteroid related iatrogenic injury/bone loss assessment; (4) Influenza immunization; (5) Pneumococcal immunization; (6) Testing for latent TB before initiating anti-TNF therapy; (7)Assessment of hepatitis B status prior to initiating anti-TNF therapy; (8) Tobacco user screening and cessation intervention. These core measures have been validated by literature review and multidisciplinary expert panel, and physician ratings and payments are anticipated to be based on outcome measures and documented adherence to practice guidelines. Previous data have suggested that IBD patients may not be receiving optimal care even at tertiary centers. To date, there have been no studies investigating provider documentation, and therefore adherence to practice guidelines. Methods: A retrospective chart review of IBD patients seen in the outpatient setting in Carolinas HealthCare Gastroenterology Clinics from January 2011 to April 2014 was performed. Hundred patient charts were randomly selected based on ICD-9 diagnosis codes. Rates of gastroenterology provider (MD or PA) documentation of outpatient core measures were performed on clinic notes. Results: The data included 58 patients with CD and 42 patients with UC. Complete type, location and activity were documented in 77% of patients. Intermittent systemic steroids had been prescribed in 25% of patients. 22% were on anti-TNFs, and 20% were prescribed thiopurines. Of the patients who had received steroids, 32% had a documented bone density assessment or one was recommended. Thirteen percent of patients had influenza immunization status and 7% had pneumococcal immunization status documented. Provider documentation of TB status on anti-TNF therapy was noted in 72% of patients. Provider documentation of Hepatitis B status was present in 68%. There were 12 documented tobacco users, and 64% had documentation of smoking cessation counseling by the GI provider. Conclusions: Documentation of outpatient IBD quality measures could be improved. Disease type, location, and activity were documented to a reasonable degree. Smoking cessation counseling is being provided but could be better emphasized. Provider documentation of TB and Hepatitis B status of patients receiving anti-TNF could be improved but is likely underestimated in this review. The area of greatest improvement is preventive care including bone loss assessment for those patients receiving systemic steroids and immunizations for all IBD patients. Understanding these deficiencies in IBD care can help guide quality improvement initiatives and improve clinical outcomes and consistency in IBD care.